The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acs.inorgchem.0c00611
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Structure and Binding Mode of EDTA on the Surface of Mn3O4 Nanoparticles for Water Oxidation by Advanced Electron Paramagnetic Resonance Spectroscopy

Abstract: Identification of the surface structure of nanoparticles is important for understanding the catalytic mechanism and improving the properties of the particles. Here, we provide a detailed description of the coordination modes of ethylenediaminetetraacetate (EDTA) on Mn 3 O 4 nanoparticles at the atomic level, as obtained by advanced electron paramagnetic resonance (EPR) spectroscopy. Binding of EDTA to Mn 3 O 4 leads to dramatic changes in the EPR spectrum, with a 5-fold increase in the axial zero-field splitti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Hausmannite (Mn 3 O 4 ) crystallizes in a tetragonal spinel-like structure ( I 4 1 / amd space group) below 1170 °C because of the Jahn–Teller effect . It has attracted great interest for its potential technological applications in electrocatalysis and water treatment. It is hypothesized that the Mn­(III) instead of Mn­(II) or Mn­(IV) at the surface are more active catalytically . However, the surface structures are still to be revealed …”
mentioning
confidence: 99%
“…Hausmannite (Mn 3 O 4 ) crystallizes in a tetragonal spinel-like structure ( I 4 1 / amd space group) below 1170 °C because of the Jahn–Teller effect . It has attracted great interest for its potential technological applications in electrocatalysis and water treatment. It is hypothesized that the Mn­(III) instead of Mn­(II) or Mn­(IV) at the surface are more active catalytically . However, the surface structures are still to be revealed …”
mentioning
confidence: 99%
“…S7 †). 51 IR analysis and PXRD showed that there was no significant change after illumination (Fig. S8 †), which ruled out the possibility of photoisomerization and photodecomposition.…”
Section: Paper Dalton Transactionsmentioning
confidence: 97%